2021
DOI: 10.2147/jir.s284889
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Biomarkers and Molecular Targets Among JAK Family in Breast Cancer

Abstract: Background: Janus kinases (JAKs) are a family of non-receptor tyrosine kinases involved in multiple malignancies. However, clinical values of JAKs as prognostic markers and potential mechanism as molecular targets in breast invasive carcinoma (BC) are not completely clarified. Methodology: TIMER, UALCAN and GEPIA were used to assess the expression and methylation levels of JAKs in BC. Kaplan-Meier Plotter, bc-GenExMiner, SurvExpress, TRGAted, MethSurv, and SurvivalMeth were used to assess the multilevel progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
2
6
0
Order By: Relevance
“…This is in line with the results of univariate analysis in the current study, confirming metastasis formation, lymph nodular status, and TYK2 expression to be predictors of survival. This was similar in other malignancies, including breast cancer ([ 26 ]) and lung adenocarcinoma ([ 28 ]), while other studies found TYK2 overexpression to be related to worse survival, e.g., in stomach adenocarcinoma ([ 29 ]). TYK2 has different potentially relevant functions in cancer and metastasis formation; stimulation of proliferation and protection from cell death, promotion of migration and invasion, and metastasis formation could be important factors regarding survival in different cancer entities ([ 30 ]).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is in line with the results of univariate analysis in the current study, confirming metastasis formation, lymph nodular status, and TYK2 expression to be predictors of survival. This was similar in other malignancies, including breast cancer ([ 26 ]) and lung adenocarcinoma ([ 28 ]), while other studies found TYK2 overexpression to be related to worse survival, e.g., in stomach adenocarcinoma ([ 29 ]). TYK2 has different potentially relevant functions in cancer and metastasis formation; stimulation of proliferation and protection from cell death, promotion of migration and invasion, and metastasis formation could be important factors regarding survival in different cancer entities ([ 30 ]).…”
Section: Discussionsupporting
confidence: 77%
“…Survival is a critical outcome parameter of HNSC; thereby, majority of recurrence or disease-specific deaths take place within 2-3 years since diagnosis ([ 25 ]). TYK2 has previously been found to be related to autoimmunity ([ 15 – 17 ]) and various cancers ([ 24 , 26 , 27 ]). A previous study on laryngeal squamous cell carcinoma found that lower TYK2 would be significantly associated to worse overall survival ([ 24 ]), which is in line with the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these hub genes (CXCL1, DDX58 and JAK3) have been reported to be targets of DNA methylated modification in schizophrenia, 38 hand, foot and mouth disease (HFMD), 39 and breast cancer. 40 The present results further suggested functional DNA methylation modification in these hub genes might play a crucial role in CS-induced airway inflammation in COPD.…”
Section: Discussionsupporting
confidence: 67%
“…To approximate the abundance of TIIGs, the TIMER database uses TCGA data for 10,897 samples across 32 types of cancer. To assess the relative variations in gene expression amongst sets in the samples [ 11 , 12 ], we used a deconvolution algorithm based on gene expression called CIBERSORT ( http://cibersort.stanford.edu/ ). With CIBERSORT, we measured the immune response of 22 TIICs to evaluate their association with the risk grouping in lung cancer and to reveal correlations amongst TIICs.…”
Section: Methodsmentioning
confidence: 99%